Yeast dynamics during the natural fermentation process of table olives (Negrinha de Freixo cv.) - Pereira, Ermelinda (2018)
Yeast population and dynamics associated to spontaneous fermentation of green table olives Negrinha de Freixo cv. were evaluated. Olives and brine samples were taken at different fermentation times, and yeast were enumerated by standard plate count and identified by sequencing of the internal transcribed spacer (ITS) region of the nuclear ribosomal DNA (rDNA). Saccharomyces cerevisiae was the most frequent, followed by Candida tropicalis, Pichia membranifaciens and Candida boidini, representing together 94.8% of the total isolates. Galactomyces reessii was also identified for the first time in table olives. The highest species diversity was found between 44 and 54 days of fermentation, both in brine and olive pulp. Furthermore, high similarity was observed between brine and olive pulp microbiotas. In conclusion, these results give valuable information to table olive industrials in order to achieve more knowledge on the fermentation process of this important Protected Designation of Origin product.